Rewilding in Southeast Asia: Singapore as a case study. Issue 3 (15th February 2023) - Lamperty, Therese; Chiok, Wen Xuan; Khoo, Max D. Y.; Amir, Zachary; Baker, Nick; Chua, Marcus A. H.; Chung, Yi Fei; Chua, Yen Kheng; Koh, Joshua J.‐M.; Lee, Benjamin P. Y.‐H.; Lum, Shawn K. Y.; Mendes, Calebe P.; et al.
Abstract: Re‐establishing extirpated wildlife—or "rewilding"—is touted as a way to restore biodiversity and ecosystem processes, but we lack real‐world examples of this process, particularly in Southeast Asia. Here, we use a decade of aggregated camera trap data, N ‐mixture occupancy models, and input from local wildlife experts to describe the unassisted recolonization of two native large herbivores in Singapore. Sambar deer ( Rusa unicolor ) escaped from captivity (in private or public zoos) in the 1970s and contemporary camera trap data show they have only colonized nearby forest fragments and their abundance remains low. Wild pigs ( Sus scrofa ), in contrast, naturally recolonized by swimming from Malaysia in the 1990s and have rapidly expanded their range and abundance across Singapore. While wild pigs have not recolonized all viable green spaces yet, their trajectory indicates they soon will. We also note that a third ungulate, the muntjac deer ( Muntiacus muntjak ), was captured in camera trapping in 2014 and 2015 but was never recorded afterward despite increased sampling effort, and thus we do not focus on their presumably unsuccessful recolonization. The divergent rewilding trajectories between sambar deer and wild pigs suggest different conservation outcomes and management requirements. Sambar deer may restore lost plant–animal interactions such as herbivory and seed dispersal without requiring significant management. Wild pigs, in contrast, have reached high numbers rapidly and may require active management to avoid hyperabundance and negative ecological impacts in regions, such as Singapore that lack both hunting and large predators.